Hyers-Ulam Stability of Third Order Euler's Differential Equations. (3rd November 2014) - Tripathy, A. K.; Satapathy, A.
Abstract : We investigate the Hyers-Ulam stability of third order Euler's differential equations of the form t 3 y ' ' ' + α t 2 y ' ' + β t y ' + γ y = 0 on any open interval I = ( a, b ), 0 < a < b ≤ ∞ or - ∞ < a < b < 0, where α, β, and γ are complex constants.